2019
DOI: 10.7600/jpfsm.8.113
|View full text |Cite
|
Sign up to set email alerts
|

Static stretching duration needed to decrease passive stiffness of hamstring muscle-tendon unit

Abstract: Static stretching (SS) is widely used to decrease and retain the passive stiffness of the muscle-tendon unit in clinical and athletic settings. It is important to consider the minimum SS duration required to decrease the passive stiffness of the hamstring, from the perspective of injury prevention of the hamstring muscle. The purpose of this study was to investigate the time course of the effect of static stretching (SS) on passive stiffness of the hamstring and to clarify the minimum SS duration required to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…The effects of SS on muscle-tendon unit stiffness is affected by its duration [9,21] and intensity [7,8,22]. Matsuo et al [9] and Nakamura et al [21] examined the duration of SS needed to decrease muscle-tendon unit stiffness of hamstrings, and they showed that three minutes of SS was needed to decrease the stiffness. However, previous studies reported the duration of SS used as a part of a warm-up routine is approximately 20 seconds [1,23].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of SS on muscle-tendon unit stiffness is affected by its duration [9,21] and intensity [7,8,22]. Matsuo et al [9] and Nakamura et al [21] examined the duration of SS needed to decrease muscle-tendon unit stiffness of hamstrings, and they showed that three minutes of SS was needed to decrease the stiffness. However, previous studies reported the duration of SS used as a part of a warm-up routine is approximately 20 seconds [1,23].…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that ROM increased without any difference between the muscles, while vertical jump height significantly decreased after SS of only the triceps surae. The effective duration of SS required to decrease passive properties differs between each muscle 9–11. Nakamura et al reported that SS for more than 2 min is effective in increasing the extensibility of the gastrocnemius muscle 10.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al reported that SS for more than 2 min is effective in increasing the extensibility of the gastrocnemius muscle 10. Matsuo et al 9 and Nakamura et al 11 reported that more than 3 min of SS is effective on decrement in passive stiffness of the hamstrings. To our best knowledge, the effective duration of SS for the quadriceps is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations